Canadian Occupational Therapists' Use of Technology With Older Adults: A Nationwide Survey. (April 2021) - Aboujaoudé, Aline; Bier, Nathalie; Lussier, Maxime; Ménard, Christine; Couture, Mélanie; Demers, Louise; Auger, Claudine; Pigot, Hélène; Caouette, Martin; Lussier-Desrochers, Dany; Belchior, Patricia
As rehabilitation specialists, occupational therapy practitioners play a gateway role regarding recommendation of various technologies for homecare. However, no study has investigated current occupational therapy practices concerning information and communication technology (ICT) for older adults in Canada. The objective of this study was to identify Canadian occupational therapists' (OTs) knowledge and practices of ICT with older adults as well as factors associated with its recommendation. A Canada-wide, cross-sectional, online survey was conducted. Of 387 OTs, only 12.4% reported recommending ICT in practice. ICTs supporting communication and cognition were the main types recommended. The reported barriers to use in practice differed between ICT familiar users and nonusers . Multivariate logistic regression analyses showed that clinicians with more years of clinical experience were more likely to recommend ICT. Clinicians' services, work environments, and client diagnosis were also factors associated with ICT recommendation. Additional research is needed to understand how to overcome barriers to ICT recommendation in OT practice.